(untitled) (Surkhet Journal, 2025)
This study aimed to explore the administrative experiences of bureaucratic leadership in higher education in Nepal. The study was based on a qualitative research design. Participant is selected as a deputy administrator of a higher education institution purposively. I collected the narrative of the participant regarding his bureaucratic leadership experience. The stories of lived experiences were recorded, transcribed in Devanagari script and translated into English for analysis. The findings of this study indicate that the participant’s family background, particularly the moral influence of his mother, played significant role in shaping his discipline, punctuality, and collaborative approach, which are essential for effective administrative leadership. His vision of developing the academic environment was the enhancement of physical infrastructure, the development of collaboration among staff, and representing a commitment to both bureaucratic and transformational leadership practices. In the case of financial management and transparency, the participant prioritized financial self-reliance by minimizing expenditures, optimizing internal resources, and ensuring fiscal discipline to sustain institutional activities without dependence on central funding. The bureaucratic leadership approach to managing the academic environment reflected a careful effort to cultivate a supportive, politically balanced, and aesthetically enhanced learning environment through staff collaboration, adherence to bureaucratic leadership indicators, and strategies that promoted institutional development and staff motivation. This study contributes by showing how familial inspiration can shape essential leadership qualities such as discipline, promptness, and collaboration in higher education administration. It also adds to the literature by demonstrating that a leader’s clear vision and effective bureaucratic practices can enhance infrastructure, foster collaboration, and cultivate a supportive and balanced academic environment.